Coaches, parents, and peers influence on female athletes' eating behaviors - Duffy-Paiement, C.; Paiement, C. (Research Quarterly for Exercise and Sport, 2009)
Purpose: Athletes are typically competitive and disciplined individuals who expend exceptional energy on excelling in their sport. This personality type pooled with the expectations of significant others (parents, coaches and peers) and the need for lean, muscular and/or aesthetically pleasing bodies may make developing an eating disorder more likely than in non-athletes. Research on the interrelationships of athletes and significant others have revealed that peers, parents and coaches may influence both enjoyable and stressful sport experiences for the athlete. Pressuring behaviors from parents and coaches have related positively to maladaptive behaviors, self-assigned pressure and lower perceptions of competence (Ommundson et al, 2006). These issues, as well as peer influence on body dissatisfaction, have been empirically linked to eating disorders (Silverstone 1992; Steinhausen 1993; Shroff & Thompson, 2007). Parents and peers are generally found to have substantial influence on attitudes, decisions and behaviors of young adults (Majumdar, 2003). In coaching research, coaches have been connected to strong influence in regulating athletes' behaviors and attitudes (Anshel, 1990; Orlick, 1990; Dieffenbach, Gould, and Moffett, 2002). It has been argued that coaches could be one of the more important agents in influencing risky behaviors, such as performance enhancing drug use and eating disorders (Dubin, 1990). The purpose of this research is to examine the influence of significant others (i.e. coaches, parents, peers) on disordered eating, and specifically, coaches influence on athletes' eating disorders, which has not been previously examined.